Лицом к лицу с Кембриджской системой обучения - Мерхайдарова, Н.Н. (My University, 2016)
The article highlights the experience of realization of the key ideas of level modular programs in the classroom of students of pedagogical specialties. The questions of how to organize the group work, dialoguetraining, how to develop critical thinking in the classroom, and others.
Keywords: level modular programs; group work; dialogue training; critical thinking